The impact of decentralisation on public sector corruption in Indonesia - Rizqi Bachtiar (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
Corruption is one of the illnesses of the government bodies that are still being combated in some countries, especially Indonesia. In order to reduce corruption cases, there are several reforms to be implemented, for example decentralisation. Decentralisation is expected to solve the problem since the policy narrows the gap between government and citizens. However, decentralisation does not eventually reduce corruption cases. Indonesia, for example, based on Corruption Perception Index has relatively stagnant ranking of  combating corruption. Furthermore, there are few researches on the impact of decentralisation on corruption. Based on the explanation, this paper examines the drawbacks and benefits of the implementation of decentralisation on public sector corruption in Indonesia. Interestingly, this research finds that the implementation of decentralisation in Indonesia seems to have diverse impacts to eradicate corruption cases. For example, although Indonesia still has unsatisfied rank in combating corruption, the successfulness of KPK in arresting several local leaders indicates that decentralisation helps the enforcement institution in recognising the responsible actors on corruption acts. Therefore, this research is expected to fill the research gap on the impact of decentralisation on corruption in Indonesia.